2016
DOI: 10.1055/s-0036-1593445
|View full text |Cite
|
Sign up to set email alerts
|

Endothelial Progenitor Cells as a Marker of Endothelial Dysfunction and Atherosclerosis in Ankylosing Spondylitis: A Cross-Sectional Study

Abstract: Endothelial progenitor cells (EPCs) have reparative potential in overcoming the endothelial dysfunction and reducing cardiovascular risk. EPC depletion has been demonstrated in the setting of established atherosclerotic diseases. We evaluated whether reduced EPCs population are associated with endothelial dysfunction, subclinical atherosclerosis, and inflammatory markers in ankylosing spondylitis (AS) patients without any known traditional cardiovascular risk factor. We performed a cross-sectional study of 30 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
15
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(18 citation statements)
references
References 41 publications
1
15
1
1
Order By: Relevance
“…Assuming, that homing of vascular progenitor cells in sepsis involves various mediators that recruit them to activated endothelium in response to a damage-induced inflammation, we set out to determine in septic patients which adhesion molecules are expressed by CD34 + /CD133 + -stem cells—containing vascular progenitors [ 17 , 18 ]—and could therefore be involved in the CD34 + /CD133 + -stem cell-driven repair process. Furthermore, we wanted to analyse, if the upregulation of adhesion molecules by CD34 + /CD133 + -stem cells is associated with survival or mortality of septic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Assuming, that homing of vascular progenitor cells in sepsis involves various mediators that recruit them to activated endothelium in response to a damage-induced inflammation, we set out to determine in septic patients which adhesion molecules are expressed by CD34 + /CD133 + -stem cells—containing vascular progenitors [ 17 , 18 ]—and could therefore be involved in the CD34 + /CD133 + -stem cell-driven repair process. Furthermore, we wanted to analyse, if the upregulation of adhesion molecules by CD34 + /CD133 + -stem cells is associated with survival or mortality of septic patients.…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have shown arterial stiffness in patient's large arteries [11] [12]. To our knowledge, the studies have not demonstrated an increase in the common (carotid intima-media thickness) cIMT [11]. Moreover, no studies have evaluated the PWV.…”
Section: Ankylosing Spondylitismentioning
confidence: 89%
“…The literature contains less information about the assessment of endothelial function in AS [11] [12]. Several studies have shown arterial stiffness in patient's large arteries [11] [12].…”
Section: Ankylosing Spondylitismentioning
confidence: 99%
See 1 more Smart Citation
“…Тривале запалення призводить до активації та пошкодження ендотелію, є причиною атерогенезу (Taurog J.D. et al, 2016;Verma I. et al, 2017) і розвит ку гострих серцево-судинних станів, при яких атеросклеротична бляшка дестабілізується і розривається, що призводить до тромбоутворення (Teupser D. et al, 2011). Саме тому запалення набуває особливого значення в розвитку ЕД та серцево-судинної патології в пацієнтів з автоімунними захворюваннями, постійним атрибутом яких є власне персистуюче системне запалення (Syngle A. et al, 2010).…”
Section: вступunclassified